Management of field and in vitro germplasm collections. Proceedings of a consultation meeting, 15-20 January 1996, CIAT Cali, Colombia - Engelmann, F. (1999)
The meeting examined the role of field and in vitro germplasm collections in strategies to conserve and use clonally propagated crops, problems and constraints in their management, and the complementarity of field and in vitro germplasm collections. The meeting produced a list of key issues to address in the establishment, maintenance and use of field and in vitro germplasm collections, and in the integration of the two conservation methods in a complementary manner. The meeting also recommended to develop general guidelines for the management of field and in vitro germplasm collections, which should identify key issues and provide genebank curators with decision criteria and options in establishing, maintaining and using field and in vitro germplasm collections. These guidelines are currently being finalized and will be published in the near future.